# Use the distributive property to multiply: A) (3x+2y-1)(-xy)B) 5/6(12x^2-24x+18)

### 1 Answer | Add Yours

Distributive property requires that the term - in this case (-xy)- be "distributed" within the other bracket and multiplied individually, thus:

(3x + 2y - 1)( -xy)

= 3x(-xy) + 2y(-xy) -1(-xy)

= `-3x^2y + (-2xy^2) - (-xy)`

= `-3x^2y - 2xy^2 + xy`

I am not permitted according to eNotes rules to answer multiple questions. Apply the same method to your second question, refer to the link below or post your question separately.

A) = `-3x^2y - 2xy^2 + xy`